LEGAL PROBLEMS OF ABORTION CRIMINAL ACT IN LAW NUMBER 1 OF 2023 REVIEWED FROM THE INTERNATIONAL COVENANT ON CIVIL AND POLITICAL RIGHTS (ICCPR) - Eva Serevina Sinaga; T Riza Zarzani (PT. Sinergi Legal Publisher, 2024)
This study compares Indonesia's abortion regulation under Law No. 1 of 2023 with principles outlined in the International Covenant on Civil and Political Rights (ICCPR). Indonesia criminalizes abortion with strict exceptions, such as cases involving rape or medical emergencies. The law reflects religious and cultural values ​​rooted in the nation's Pancasila ideology, emphasizing the sanctity of life. In contrast, the ICCPR advocates for broader protections for individual rights, including bodily autonomy and health in reproductive contexts, without discrimination. While both frameworks aim to protect life, Indonesia's approach enforces specific legal and moral criteria before permitting abortion, potentially limiting access for women in challenging circumstances. This study reveals the legal and ethical balance required for abortion regulation in Indonesia, highlighting tensions between national values ​​and international human rights standards.